Drosophila Modeling of Heritable Neurodevelopmental Disorders - Gatto, Cheryl L. (2011)
Heritable neurodevelopmental disorders are multifaceted disease conditions encompassing a wide range of symptoms including intellectual disability, cognitive dysfunction, autism and myriad other behavioral impairments. In cases where single, causative genetic defects have been identified, such as Angelman syndrome, Rett syndrome, Neurofibromatosis Type 1 and Fragile X syndrome, the classical Drosophila genetic system has provided fruitful disease models. Recent Drosophila studies have advanced our understanding of UBE3A, MECP2, NF1 and FMR1 function, respectively, in genetic, biochemical, anatomical, physiological and behavioral contexts. Investigations in Drosophila continue to provide the essential mechanistic understanding required to facilitate the conception of rational therapeutic treatments.